The Modern Trends in Internal Auditing and Their Role in Enhancing the Efficiency and Effectiveness of Performance in Governmental Units - Layla Naji Majeed AL Fatlawi (Newinera Publisher, 2024)
This research aims to explore and analyze the modern trends of internal auditors in the Iraqi public sector and their role in enhancing the efficiency and effectiveness of performance, with the objective of developing their professional practices. It examines how recent advancements, such as advanced technology and risk-based practices, improve the efficiency and effectiveness of internal auditing within the governmental environment. The study provides data-supported recommendations for policymakers and managers in governmental units to enhance transparency and efficiency through the adoption of best global practices. To achieve the research objective, the researcher designed a questionnaire containing (47) variables distributed across three axes. The first axis (fundamental trends of internal auditing) included (22) items covering aspects of this axis. The second axis (the contemporary role of internal auditing in risk management) comprised (3) main items and (15) sub-items covering all variables of this axis. The third axis (the reflection of internal auditing in improving the efficiency and effectiveness of the economic unit) included (10) items. The study reached several conclusions, the most significant being that internal auditing according to modern trends is not limited only to assessing compliance and financial control, but its role extends to vital aspects such as risk classification, risk management evaluation, and fraud and fraud prevention. Internal auditing is a crucial tool not only in control and compliance but also in enhancing efficiency and effectiveness within institutions.